Performance of promising wheat genotypes and sowing time for cultivation under Burma dek (Melia composita L.) based agri-silviculture system in Punjab - Singh, Ramandeep; Kaur, Navneet; Gill, R.I.S. (Indian Journal of Agroforestry, 2020)
The performance of different varieties of wheat (Triticum aestivum L.) was studied in the alleys of Burma dek (Melia composita L.) trees spaced at 7 Ã— 3 m. The treatments included environments viz., open and intercropping with dek, four wheat varieties viz., HD 2967, WH 1105, PBW 677 and PBW 725 sown on three different times i.e. 25th October, 10th November and 25th November in 2015 under 3 years old block plantation of Burma dek. The experiment was laid out in split-split plot design and data were recorded in three replications for each treatment including tree and tree-less plots. Micro-climatic parameters influencing the understory crop growth and yield like surface air temperature, relative humidity and photosynthetically active radiation were observed in open and intercropped conditions. There was reduction of 21.4% in average wheat yield intercropped with 3 years old dek block plantation as compared to open. Late sowing of wheat crop drastically reduced the crop growth (plant height, tillers/m2 and dry matter) and yield attributes (spike length and number of grains/spike) under dek and open. Wheat sown on 25th October, reported maximum growth and yield attributes which was statistically at par with 10th November and significantly higher than 25th November. The 25th October sown crop had highest grain yield (4.90 Mg ha-1) which was at par with 10th November (4.35 Mg ha-1) and significantly better than 25th November under dek. Amongst wheat varieties, PBW 725 recorded highest grain yield i.e. 4.91 Mg ha-1 which was statistically at par with PBW 677 (4.67 Mg ha-1) and significantly better than rest of the varieties. Hence, it may be concluded that wheat varieties, PBW 725 and PBW 677 are suitable for intercropping with dek block plantation and these should be sown during 25th October to 10th November for higher yield.